Performansi Software Defined Networking Menggunakan Openflow Pada Jaringan Politeknik Caltex Riau - Ahmad Fauzan (Politeknik Caltex Riau, 2021)
Software Define Network (SDN) is a network technology in which parts of the device infrastructure, namely the control plane and data plane, are separated, so that routing policies can be carried out centrally through the controller. The controller used is OpenDaylight. SDN will be combined with OpenFlow which will make network operators easy to operate. SDN is an architecture that can design, manage and implement. SDN architecture is applied to Mikrotik devices to compare the quality of service (QoS) between SDN architecture and architecture without SDN (traditional). The results of the measurement of quality of service (QoS) obtained with the throughput value is 248,53515625, then the packet loss value obtained is 0, the delay value is 0,000016558 and the jitter value is 0,996741045. The measured throughput ,packet loss and delay values are very good values according to the value category of each parameter, but the measured jitter are poor based on the value category of each parameter Keywords: Software Defined Networking, Throughput, Packet Loss, Jitter, Delay.